Estudo biomecânico de coluna torácica de adolescente, em cifose e hipocifose, sob carregamento ligamentar assimétrico: uma possível predição da escoliose idiopática - Rozilene Maria Cota Aroeira (2017)
This doctoral thesis in the field of Biomedical Engineering integrates principles of natural and health sciences. Specifically, the aim of the work was to test a 3D geometric model of the spine, generated from a 3D modeling software using graphical images, as an alternative technique in a biomechanical study of the spine using the Finite Element Method (FEM). A study of the thoracic spine, with characteristics of adolescent spine, was conducted to better understand the biomechanical behavior of this structure when its physiological curvature is altered and relate it to the spine deformity known as Adolescent Idiopathic Scoliosis (AIS). For decades, the scientific community has put great efforts to determine the pathogenesis of this highly deforming pathology, which affects 2% to 4% of adolescents worldwide. A biomechanical pilot study with the normal T7-T8 vertebral segment was conducted to test the 3D model generated from graphical images, by numerical analysis using FEM. In this segment, the displacement field of bone structures and of the intervertebral disc was analyzed, in addition to the stress field. The results were compared to previous experimental studies with the aim of validating the method. In addition, the study included modeling and biomechanical simulation using FEM of the T5-T10 mid-thoracic segment (segment with the highest incidence of vertebral deformities in youth). Two models of this vertebral segment, with physiological curvature (kyphosis) and curvature reduction (hypokyphosis), were analyzed under axial load associated with the presence of ligament asymmetry and the results were subsequently associated with the process of idiopathic scoliosis onset. Numerical analysis using FEM showed that the use of graphics 3D modeling was satisfactory for the analysis of displacement of structures, and has potential to be used in other biomechanical studies. The study showed a greater vertebral displacement and reproduction of scoliosis in the condition of hypokyphosis, at the presence of asymmetric ligament load, than in the condition of kyphosis. However, stress analysis should be further evaluated in future studies. As an appendix to the study, a method of reconstruction of the 3D model of the human body was proposed to study vertebral curvatures and body asymmetries qualitatively and quantitatively, aiming for the early screening of postural changes in individuals at the age of bone maturation. Early diagnosis has a direct impact on the prevention of the severity of vertebral deformities. The images obtained are innovative cost-effective, portable, and threedimensionality.